Peran Komunikasi Organisasi dalam Meningkatkan Kinerja Karyawan - Rhyo R. Dami Dato; Lukas L. Daga; Monika Wutun (Universitas Nusa Cendana, 2019)
The purpose of this study was to determine the Role of Organizational Communication in improving the performance of employees of the Dutalia Oesapa Supermarket in Kupang City. The theory used in this study is the theory of human relations. This research is a qualitative study with research procedures that produce descriptive data. The informants in this study were determined by the principle of adequacy and conformity. Test the validity of the data using qualitative data analysis of Milles & Huberman. The results of the study found that the role of communication applied to Dutalia Oesapa Kupang went well in improving employee performance. Dutalia Oesapa Kupang employees must know and be able to apply the Guest Service Cycle (GSC) as a standard employee service cycle so that communication between leaders and fellow employees can be well established and each employee still feels valued and cared for by the leadership and fellow employees, and there is no the gap between senior workers and general workers in order to improve good employee performance so that they know about how communication takes place through various stages that are carried out continuously, change, and there is no end in order to deliver messages. Employee Performance at Dutalia Oesapa Kupang is a real achievement achieved by a person both in quality and quantity that an employee achieves in carrying out his duties in accordance with the responsibilities given. Organizational communication in Dutalia Oesapa Kupang should apply the human relations theory that must have work performance evaluations for all employees within the organization, so that the organization can know the extent of achievement levels. This can be used as a benchmark for giving compensation in making innovations that will improve employee performance.